Biomarkers of stroke recovery: consensus-based core recommendations from the Stroke Recovery and Rehabilitation Roundtable - Boyd, Lara A.; Hayward, Kathryn S.; Ward, Nick S.; Stinear, Cathy M.; Rosso, Charlotte; Fisher, Rebecca J.; Carter, Alexandre R.; Leff, Alex P.; Copland, David A.; Carey, Leeanne M.; Cohen, Leonardo G.; Basso, D. Michele; et al. (Sage, 2017)
The most difficult clinical questions in stroke rehabilitation are ‘‘What is this patient’s potential for recovery?’’ and ‘‘What is the best rehabilitation strategy for this person, given her/his clinical profile?’’ Without answers to these questions, clinicians struggle to make decisions regarding the content and focus of therapy, and researchers design studies that inadvertently mix participants who have a high likelihood of responding with those who do not. Developing and implementing biomarkers that distinguish patient subgroups will help address these issues and unravel the factors important to the recovery process. The goal of the present paper is to provide a consensus statement regarding the current state of the evidence for stroke recovery biomarkers. Biomarkers of motor, somatosensory, cognitive and language domains across the recovery timeline post-stroke are considered; with focus on brain structure and function, and exclusion of blood markers and genetics. We provide evidence for biomarkers that are considered ready to be included in clinical trials, as well as others that are promising but not ready and so represent a developmental priority. We conclude with an example that illustrates the utility of biomarkers in recovery and rehabilitation research, demonstrating how the inclusion of a biomarker may enhance future clinical trials. In this way, we propose a way forward for when and where we can include biomarkers to advance the efficacy of the practice of, and research into, rehabilitation and recovery after stroke.